Grindability Studies on Monel under Different Cooling Environments. (2018) - Khandke, S.P.; Surve, A.; Patil, D.; Balan, A.S.S.; Kuppan, P.; Oyyaravelu, R.
Abstract: Monel-400 is a Nickel based super alloy which comes under the category of Difficult To Grind material (DTG) due to its significant properties like high hardness, high hot strength, high strain hardening and less thermal conductivity. The lubrication system in grinding process requires a continuous monitoring of the quality of emulsion to resists a desired grinding environment and it is necessary to maintain an effectively lubricated wheel-work interface. The current study aims to assess the grindability of Monel under various grinding environment such as cold air, Minimum Quantity Lubrication(MQL) and MQL with cold air. Along with it, grinding force, temperature, surface roughness, coefficient of friction was also measured. The results show, grinding with combination of MQL with cold air lowers the temperature to great extent. The surface roughness (Ra ) value for MQL with cold air condition is 45–50% less over dry grinding, 35–38% less over cold air condition & 7–10% less over MQL cooling environment. Also, lesser value of coefficient of friction (µ), indicates the ease of grinding operation. Chemical affinity between wheel and workpiece interface, traces of workpiece material sticking to abrasive wheel was also observed.